12a- 6a + a = 7a Since they all have the same variable, you can simply add and subtract 12-6 = 6 6+1 = 7
6a
98a + 5 + 6a = 104a + 5
6a - 8 - 4a - 2 → 6a - 4a - 8 - 2 → 2a - 10
-6a + 8 = 2 -6a = -6 a = 1
2a² + 6a
12a- 6a + a = 7a Since they all have the same variable, you can simply add and subtract 12-6 = 6 6+1 = 7
11a+7b-(3b-2a)
21a - 6a
(a^2+7a-8)/(a^2+6a-7) (original equation) (a+8)(a-1)/(a+7)(a-1) (simplify top and bottom) (a+8)/(a+7) <--answer
6
12a2/(2ab) = 6a/b
6a
54qba
Divide by 6a: 6a(a + 3b)
It is 6a + 12, an expression which cannot be evaluated without the value of a.
6ax2 + 6ax + 6a = 6a(x2 + x + 1)